Integration Of Roblox Game As A Gamification Media For Developing Bartender Competence In Culinary Vocational Education: A Systematic Review - Aditia Gustiana Gunawan; Alvina Fadila Maulida; R. Machmud Sugandi; Gina Khoirunnissa (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2025)
This research uses the PRISMA 2020 review guideline to systematically review literature (2015–2025) related to Roblox and gamification-based environments in vocational culinary education that support bartender skills acquisition of cocktail and mocktail making. A review of 20 academic research papers shows that Roblox is associated with improved student engagement, procedural accuracy, creativity and professional skill development especially when combined with gamification elements like leaderboards, rewards and collaborative learning. Practical skills and motivation to learn are greatly enhanced in hospitality and culinary training contexts through video games or simulations. Yet, there remain several challenges to overcome including technology divide, expense of infrastructure; teacher preparedness and non-standardized assessment. In general, these results highlight the transformative nature of Roblox as a new medium for refreshing bartender pedagogy and call attention to opportunities and tensions that warrant further investigation in terms of scalability, long term retention retention,, and industry relevant assessment frameworks.